THE DEVELOPMENT OF GAMMA RADIATION DOSIMETERS REAL-TIME NETWORK-BASED SENSOR WIRELESS IEEE 802.15.4 PROTOCOL: The Dosimeters Real Time Base on WSN - Ramacos Fardela (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Several studies have been carried out on the development of real-time gamma radiation dosimeter based on the wireless sensor network (WSN) protocol IEEE 802.15.4. WSN technology can be adopted to develop a gamma radiation dose monitoring system on a large scale due to its real-time, centralized, efficient, and relatively low-cost attributes. This study aims to develop a personal radiation dosimeter that can collect data from the measurement results of several sensor nodes or multi-sensors. The measurement results of radiation dose values from many radiation workers are sent to a coordinator node consisting of the Xbee module and Arduino as a microcontroller. The system test is compared with a calibrated dosimeter reading and is expected to be one of the instruments for determining radiation dose in real-time. It can also reduce the risk of receiving a radiation dose that exceeds the threshold allowed by the ionizing control agency and a program in radiation protection. Changes in the intensity of radiation emitted by Cs-137 (gamma radiation) are carried out by varying each detector's distance to the source, which indirectly varies the value of the dose rate received by the detector. This relationship is shown from the value of R2 = 0.99, which indicates a strong correlation between changes in the dose given to the detector's response being developed. The system built is efficient, inexpensive, and collecting radiation exposure data can monitor radiation exposure received by workers in real-time. This technique can help speed up reporting of radiation exposure received by radiation workers.